Autocloning and Amplification of LIP2 in Yarrowia lipolytica - Pignède, Georges (American Society for Microbiology, 2000)
We synthesized a Yarrowia lipolytica strain overproducing lipase for industrial applications by using long terminal repeat (ζ) of the Y. lipolytica retrotransposon Ylt1 and an allele of URA3 with a promoter deletion to construct JMP3. JMP3 is a derivative of plasmid pHSS6 carrying a NotI-NotI cassette which contains a defective URA3 allele, a polylinker sequence, and the ζ region for targeting to multiple sites in the genome of the recipient. We inserted the LIP2 gene (encoding extracellular lipase) under the control of the strong POX2 promoter into JMP3 to generate JMP6. The pHSS6 region was removed by NotI digestion prior to transformation. Two Y. lipolytica strains transformed with the JMP6 LIP2 cassette had a mean of 10 integrated copies devoid of the Escherichia coli region, corresponding to an autocloning event. The copy number in the transformants was stable even after 120 generations in nonselective and lipase-inducing conditions. The resulting strains could produce 0.5 g of active lipase per liter in the supernatant, 40 times more than the single-copy strain with the LIP2 promoter. This work provides a new expression system in Y. lipolytica that results in strains devoid of bacterial DNA and in strains producing a high level of lipase for industrial uses, waste treatment, and pancreatic insufficiency therapy.